Primary Adenosquamous Carcinoma of the Liver on FDG PET/CT. (December 2021) - Filizoglu, Nuh; Oksuzoglu, Kevser; Ozguven, Salih
Abstract : Abstract: Primary adenosquamous carcinoma (ASC) of the liver is a rare subtype of intrahepatic cholangiocarcinoma. Hepatic ASC consists of both adenocarcinoma and squamous cell carcinoma components. Because hepatic ASC is extremely rare, only a few cases describing the imaging findings of hepatic ASC were reported before. Herein, we present FDG PET/CT findings of hepatic ASC in a 78-year-old woman who was admitted to hospital with a 4-week history of right upper quadrant pain.